On the influence of fatty acid chain unsaturation on supramolecular gelation of aminocarbohydrate-based supra-amphiphiles - Cassimiro, Douglas L. [UNESP]; Ferreira, Leonardo M. B. [UNESP]; de Souza, Ana Luiza R. [UNESP]; Fonseca, Mariana [UNESP]; Kurokawa, Suzy S. S. [UNESP]; Alonso, Jovan D. [UNESP]; Sarmento, Victor Hugo V.; Ribeiro, Clovis Augusto [UNESP] (Springer Nature, 2018)
Supramolecular gels are soft materials formed mainly by low molecular weight units held together by intermolecular interactions. Stabilizing these kinds of materials is quite a challenge due to the influence of multiple factors interfering with the integrity of the supramolecular structure. In our previous studies, we have shown that the aminocarbohydrate meglumine (MEG) interacts with organic acids by ion-pairing leading to the formation of MEG–carboxylate adducts. These adducts undergo supramolecular polymerization by heat treatment, but the macromolecular assembly was stable for a short period due to hydrogen bond (H-bond) breakup. Herein, we attempt to study the influence of hydrophobic building blocks on the formation of these compounds aiming to stabilize H-bonds to produce polymerizable supra-amphiphiles in water. Oleic acid and stearic acid are two analogous fatty acids differing only in the presence of unsaturation that were used in our studies. Results demonstrated that the presence of unsaturation hinders gelation in water by interfering with the self-assembly behavior of supra-amphiphiles. Thus, unsaturated supra-amphiphiles behave like traditional surfactants and gelify water at high concentrations (above 30% w/w). On the other hand, supramolecular gels with a polymer-like behavior could be produced with a saturated supra-amphiphile in water (above 4% w/w). The material was characterized by a lamellar arrangement that facilitates the alignment of H-bonds necessary to stabilize the self-assembled structure. These results have pivotal importance on the design of polymerizable supra-amphiphiles and demonstrate that the double bond of hydrophobic building blocks is an important design factor to be considered by scientists studying similar materials.
Keywords: Double bond; Fatty acids; Meglumine; Molecular design factors; Supramolecular amphiphiles; Supramolecular gelation